Competition volume and changes in countermovement jump biomechanics and motor signatures in female collegiate volleyball players - Kipp, K.; Kiely, M.; Geiser, C. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to investigate the relationship between competition volume and preseason to postseason changes in countermovement jump (CMJ) biomechanics and motor signatures in female collegiate volleyball players. Ten National Collegiate Athletic Association Division I female volleyball players performed CMJs on force plates before (PRE) and after (POST) their season. Countermovement jump height was calculated, and 4 discrete biomechanical variables (peak body-mass normalized force [PeakF], peak body-mass normalized rate of force development [PeakRFD], movement time [TIME], and the ratio between eccentric and total movement time [EccT:TIME]) were calculated. A factor analysis of the 4 biomechanical variables was used to identify CMJ motor signatures. The total number of sets played by each player was used to define total competition volume for the season. Correlation coefficients were used to investigate the associations between competition volume and changes in CMJ height, discrete biomechanical variables, and the components of the CMJ motor signature. The statistical analysis indicated that team-average jump height did not change over the course of the season. However, competition volume was negatively associated with changes in CMJ height, such that decreases in CMJ height over the course of the season occurred in players who played large numbers of sets. Although CMJ during POST testing was characterized by longer TIME and greater PeakRFD, CMJ motor signatures did not change and suggest that the female volleyball players in this study retained their preferred jumping strategy across the season. Given that decreases in CMJ height were most pronounced in players who played the most sets, and scored the most points during the season, future research may need to focus on player- or position-specific interventions that help players retain CMJ performance in the face of the competitive demands of a collegiate volleyball season.